Convergence of linear processes generated by negatively dependent random variables under sub-linear expectations - Mingzhou Xu; Kun Cheng; Wangke Yu (Journal of Inequalities and Applications, 2023)
Abstract In this paper, we study the complete convergence and complete moment convergence of linear processes generated by negatively dependent random variables under sub-linear expectations. The obtained results complement the ones of Meng, Wang, and Wu (Commun. Stat., Theory Methods 52(9):2931–2945, 2023) in the case of negatively dependent random variables under sub-linear expectations.